1956
DOI: 10.1098/rspa.1956.0181
|View full text |Cite
|
Sign up to set email alerts
|

The thermal conductivity of dielectric crystals: the effect of isotopes

Abstract: Measurements of the thermal conductivity of TiO 2 , KCl, LiF and of three types of diamond below room temperature are reported. Although the first three crystals were very pure there are great deviations from the form of conductivity curve predicted by Peierls for perfect crystals. A consideration of these and other results suggests that the conductivity of many crystals which have been measured is limited by the existence of more than one isotopic species of the chemical elements invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1971
1971
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…We show the first observation of transverse SSE response, which might solve the controversial question of whether or not a true TSSE exists in metallic FM films. [41] 25 [42] 135 for Si [39] ; 2 to 5 for SiN [40] …”
Section: T(cold)]mentioning
confidence: 99%
“…We show the first observation of transverse SSE response, which might solve the controversial question of whether or not a true TSSE exists in metallic FM films. [41] 25 [42] 135 for Si [39] ; 2 to 5 for SiN [40] …”
Section: T(cold)]mentioning
confidence: 99%
“…Specifically, if each solid solution compound contains p distinct crystallographic sub-lattice sites and several different ions, j, can occupy each of these sites, the mass disorder is related to the concentration of the different ions on each crystallographic site and the scattering cross-section is given by the expression [23], [24], [25]: (4) where n is the total number of atoms in the unit cell, ni is the number of atoms on the sub-lattice, i, is the mean mass of the unit cell, is the mean mass on the i-th sub-lattice and is the phonon scattering coefficient from mass variance on the i-th sub-lattice. The variance of the masses on each sub-lattice, in effect the "mass disorder", in equation In addition to the effects of phonon scattering from point defects, the thermal conductivity also scales as the inverse square root of the mean atomic mass of the compound [26].…”
Section: Discussionmentioning
confidence: 99%
“…The properties of TiO 2 nanostructures vary substantially with the synthesis method [42] and large collections of studies and achievements have been reported regarding their electrical and thermal properties and how they are influenced by various TiO 2 nanostructures. Berman and Forster [43] conducted measurements on the thermal conductivity of several dielectric crystals including TiO 2 rutile. They concluded that limitations in the isotopic species of the chemical elements in the crystal caused it to behave differently from the Peierls predicted thermal conductivity curve for perfect crystals.…”
Section: Introductionmentioning
confidence: 99%